2002
DOI: 10.1029/2002jb001777
|View full text |Cite
|
Sign up to set email alerts
|

Global surface wave diffraction tomography

Abstract: [1] We determine the effect of replacing geometrical ray theory in surface wave tomography with scattering theory. We describe a tomographic method based on a simplified version of the scattering sensitivity kernels that emerge from the Born or Rytov approximations in which surface wave travel times are a weighted average of phase or group slowness over the first Fresnel zone of the wave. We apply this ''diffraction tomography'' to Rayleigh and Love wave group velocity measurements to produce group velocity ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
215
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(229 citation statements)
references
References 48 publications
12
215
1
1
Order By: Relevance
“…One particular consequence of the very strong deviations at short period is that it may be so large that taking into account finite frequency effects based on kernels or Fresnel zones (e.g. Wang & Dahlen 1995;Ritzwoller et al 2002;Yoshizawa & Kennett 2002;Zhou et al 2004) around the great-circle may be inadequate. The data from the present study should allow better quantifying and possibly fostering tools to correct for these effects.…”
Section: O N C L U S I O N S a N D Discussionmentioning
confidence: 99%
“…One particular consequence of the very strong deviations at short period is that it may be so large that taking into account finite frequency effects based on kernels or Fresnel zones (e.g. Wang & Dahlen 1995;Ritzwoller et al 2002;Yoshizawa & Kennett 2002;Zhou et al 2004) around the great-circle may be inadequate. The data from the present study should allow better quantifying and possibly fostering tools to correct for these effects.…”
Section: O N C L U S I O N S a N D Discussionmentioning
confidence: 99%
“…The tomography method is that of Barmin et al [2001], which approximately accounts for the spatially extended frequency-dependent sensitivity of the waves by using Gaussian lateral sensitivity kernels. Although the use of spatially extended sensitivity kernels has only a small effect on the estimated maps at the periods considered [Ritzwoller et al, 2002], they help to provide a more accurate estimate of spatial resolution. This scalar quantity, instead of being obtained using the information from the resolution matrix, is determined as follows: for each grid point of the model we constructed a resolution kernel, which is a row of the resolution matrix, and we fit a 2-D spatial Gaussian function to the kernel and identified the resolution as twice the standard deviation of the Gaussian.…”
Section: Methodsmentioning
confidence: 99%
“…Significant derivations from great-circle propagation have been observed for shorter period (b40 s) surface waves (Alsina et al, 1993;Cotte et al, 2000), but surface wave ray tracing in earth models (Yoshizawa and Kennett, 2002) similar to the one presented here confirms that off-great circle propagation can reasonably be neglected for the fundamental and first few higher modes at periods greater than ∼40s and for paths less than ∼10,000 km. Ritzwoller et al (2002) examined the effects of off-great circle propagation and found that for short path lengths (∼5000 km) such as those primarily used in this study, the great circle assumption was adequate but led to increasing bias in the inverted model as path length increased. Sieminski et al (2004) show that using a dense path coverage of relatively short paths and assuming ray theory, it is possible to detect heterogeneity with length scales smaller than the wavelength of the data set.…”
Section: Seismic Constraints On the Upper Mantle Beneath Southern Africamentioning
confidence: 99%